Review articlePrismatic adaptation and its application to rehabilitation of patients with unilateral visuo-spatial neglect - Grzybkowska, Anna (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2009)
This article presents prismatic adaptation, an experimental method used in rehabilitation of unilateral neglect and some potential directions of future research. Experimental research are not coherent in conclusions, but they suggest positive effects of prismatic adaptation. We are not sure how long this effects may last. No previous research explicitly indicate that prismatic adaptation can eliminate symptoms of unilateral neglect in relation to object likewise in relation to observer. Further research is also necessary to indicate if prismatic adaptation can eliminate other, non-spatial symptoms of neglect.